Association of AT1R polymorphism with hypertension risk: An update meta-analysis based on 28, 952 subjects. (December 2015) - Liu, Dong-Xing; Zhang, Yu-Qing; Hu, Bo; Zhang, Jianfeng; Zhao, Qiang
Background: Previous studies have shown that angiotensin II AT1 receptor gene ( AT1R ) polymorphisms are associated with the risk for hypertension. However, the results remain controversial. In the present study, we performed a meta-analysis to systematically summarize the association between AT1R genetic polymorphisms and the risk for hypertension. Methods: We searched the literature in PubMed, EMBASE, ISI Web of Science, Wanfang, and Chinese National Knowledge Infrastructure databases (CNKI) to find case-control studies on the associations of AT1R genetic polymorphisms with the risk for hypertension. The meta-analysis was performed by using RevMan 5.0 software. The association of hypertension risk with AT1R genetic polymorphism was estimated by pooled odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: Fifty-six studies involving 28, 952 subjects were included in the present meta-analysis. Our results suggest that the polymorphism (A1166C) of AT1R gene is associated with a statistically increased hypertension risk, not only in Asian populations but also in Caucasian populations. We did not find any association in African populations. Conclusions: This meta-analysis suggests that A1166C polymorphism in the AT1R gene is associated with the risk of hypertension in Asian and Caucasian populations.